The effectiveness of ketamine in medication of treatment-resistant depression - review - Patrycja Brzozowska; Klaudia Bulska; Konrad Sławek; Andrzej Piela; Jan Piotrowski; Izabela Hądzlik; Julia Biały-Karbowniczek; Bianka Nowińska; Blanka Łuczak; Katarzyna Słychan (Nicolaus Copernicus University in Toruń, 2024)
In spite of the variety of antidepressant drugs available for treating depressive disorder, treatment  resistant depression (TRD) is still prevalent among the population.  Despite being used mainly in anesthesia, and mostly phased out by more modern anesthetics, ketamine shows potential when it comes to depressive disorder treatment. We've set out to investigate the the relevant body of work to determine the efficacy of ketamine usage in patients with TRD.   Research shows that usage of ketamine used in patients with TRD leads to mood elevation, better cognitive functions, sleep and appetite. Moreover, ketamine is shown to decrease suicidal thoughts and shows potential in acute actions in emergency situations, especially with its faster effects when compared to traditional antidepressants. Some research show significant reduction in suicidal thoughts after just one infusion of ketamine. Clinicians have developed intranasal, subcutaneous, intramuscular and oral ways of administering ketamine, which, though less bioavailable, when compered to intravenous use, are much more convenient and less expensive for the patients. All those ways of administering the drug have their upsides and downsides, and theres still debate on which is best. Ketamine shows promise in patients with TRD. Some studies show that up to 70% of people with TRD response to ketamine, which might show efficacy of ketamine usage in those patients   State of knowledge: Despite extensive research in the field of depression treatment, there's considerable lack of comprehensive reviews of efficacy of ketamine usage in cases where traditional ways of treating depression have failed. In the face of increasing number cases of treatment resistant depression worldwide, this paper aims to gather research papers regarding this topic and synthesize it into comprehensive review.